Adriatic Wine Amphorae in Nea Paphos - Bajlter, Marta (Études et Travaux, 2021)
The aim of this study is to present data on the amphorae and stoppers of Adriatic production coming from Cyprus, in particular from Nea Paphos. Three kinds of wine amphorae, Greco-Italic, Lamboglia 2 and Dressel 6A, closely related to each other due to a common element – a ceramic disk, which they were sealed with – appear in small amounts on sites from the late Hellenistic to the early Roman period. They are also attested at Maloutena in Nea Paphos. Analysis of these imports was carried out in order to define the quantity and variety of the material. The preliminary results were incorporated into the present paper.